Mobile Ad hoc Networks: Modelling, Application and Data Routing Evaluation - Aadri Alaa; Idrissi Najlae (International Journal of Informatics and Communication Technology (IJ-ICT), 2017)
A Mobile Ad hoc Network generally called MANET[1][2] consists of a set of mobile nodes equipped with wireless communication interfaces, forming a network without resorting to any fixed infrastructure or centralized administration, this research topic has attracted increasing interest among researchers given their characteristics and potential applications and subsets (VANET[3], WSN[4]). This paper treats both scientific and technological research aimed at presenting an in-depth study of these networks and evaluating solutions to address their problems, particularly that of routing, in order to facilitate their deployment.